A Two-Sided Dilemma: Gender Construction and The Struggle For Equality In Early Marriage In Indonesia (Program Studi Hukum Keluarga Islam, 2025)
Traditional gender stereotypes domesticate women, making their roles subordinated, marginalized, stigmatized, and burdened with multiple responsibilities while exposing them to violence. Early marriage often occurs before the legal age of 19 years as stipulated in Law Number 16 of 2019. This study examines the factors causing early marriage and its implications for fulfilling conjugal rights in Brangsong village during the first three years of marriage—a period prone to conflict. Using qualitative-descriptive methodology with a historical sociological approach and purposive sampling, the research involved early-married couples, parents, and village officials. The results revealed that the primary factor driving early marriage is adolescent curiosity about sexual intercourse motivated by dating relationships despite strong parental control, socialization, and religious knowledge. The implications for marital rights fulfillment belongedl into three categories: first, couples who responsibly work toward marriage goals with gender-equal roles; second, those using marriage to escape problems; and third, couples failing to achieve sakinah, mawadah, and rahmah due to gender inequality, resulting in divorce. This research demonstrates that successful marriages require deconstructing patriarchal frameworks and establishing equitable partnerships regardless of age.